THE CONUNDRUM OF RADIOACTIVE IODINE TREATMENT IN CONCOMITANT DIFFERENTIATED THYROID CARCINOMA AND GRAVES’ OPHTHALMOPATHY - Loh, Ee Wen; Vethakkan, Shireene Ratna; Ratnasingam, Jeyakantha; Lim, Lee-Ling; Lim, Quan Hziung; Hee, Nicholas Ken Yoong; Paramasivam, Sharmila Sunita (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Although uncommon, concomitant differentiated thyroid carcinoma (DTC) has been reported in patients with Graves’ disease (GD). Surgery is the mainstay treatment for DTC followed by radioactive iodine (RAI) ablation in selected patients. RAI therapy may pose a problem in patients with concurrent Graves’ ophthalmopathy (GO) as it may potentially worsen the ophthalmopathy. This could result in a treatment conundrum. CASES Case 1. A 63-year-old female presented with significant bilateral exophthalmos and ophthalmoplegia. She had a diffuse goiter and was thyrotoxic, with high TSH-stimulating immunoglobulin (TSI) levels. She was diagnosed as GD with sight-threatening GO. She received multiple courses of methylprednisolone as well as immunosuppressant therapy for GO. She underwent total thyroidectomy as definitive therapy. Histopathologic examination (HPE) of the thyroid gland revealed papillary thyroid carcinoma (PTC) in both thyroid lobes, with resection margin of <0.1cm in the right lobe. Following counseling for RAI ablation, she refused RAI due to the risk of worsening GO. She is currently on regular surveillance with no evidence of PTC recurrence to date. Case 2. A 41-year-old female developed moderate active GO three years after initial diagnosis of GD. She was given high-dose prednisolone for GO and underwent total thyroidectomy as definitive therapy for GD. HPE showed multifocal follicular thyroid carcinoma with suspicion of vascular permeation. After multi-disciplinary discussions, she underwent 10 fractions of ocular radiotherapy and received prophylactic prednisolone cover during RAI. On close monitoring, her GO has remained stable thus far. CONCLUSION Managing DTC in the presence of GO represents a significant challenge to the treating physician. A multidisciplinary approach and in-depth discussion with patients are essential in making treatment decisions.